The Wiley-Blackwell companion to the Anglican Communion - Markham, Ian S., ed.; Hawkins, Barney IV, ed.; Terry, Justyn, ed.; Steffensen, Leslie Nunez, ed. (West Sussex, UK : Wiley-Blackwell, 2013)
This uniquely comprehensive reference work provides a global account of the history, expansion, diversity, and contemporary issues facing the Anglican Communion, the worldwide body that includes all followers of the Anglican faith. An insightful and wide-ranging treatment of this dynamic global faith, offering unrivalled coverage of its historical development, and the religious and ethical questions affecting the church todayExplores every aspect of this vibrant religious community - from analyzing its instruments of Unity, to its central role in interfaith communication.
The Global Anglican Future Conference (GAFCON) / Mark D. Thompson.
Includes bibliographical references and index.
Keywords: Anglican Communion